Self-Regulation Abilities and Spanish-Speaking Preschoolers' Vocabulary and Letter-Word Skills in Spanish and English. Issue 2 (17th February 2017) - Palermo, Francisco; Mikulski, Ariana M.; Conejo, L. Diego
ABSTRACT: Research Findings : This study examined the heterogeneity in Spanish-speaking children's (N = 117; M age = 53 months; SD = 5 months; 57% boys) vocabulary and letter-word skills in English and Spanish after one year of preschool and the extent to which early self-regulation abilities (i.e., executive function and effortful control) were associated with that variability. Data were gathered via teacher and parent surveys and standardized assessments. Three distinct profiles of Spanish-speaking preschoolers were identified using cluster analysis. One group exhibited high levels of Spanish and English vocabulary and letter-word skills (a.k.a. high-balanced bilinguals). The other two groups exhibited predominantly Spanish or English vocabulary and letter-word skills (a.k.a. Spanish- or English-dominant). Multinomial logistic regression analyses (controlling for children's nonverbal cognitive ability) revealed that effortful control skills enhanced children's probability of being classified as high-balanced bilinguals versus Spanish-dominant; however, this was evident only for the children whose parents reported speaking exclusively Spanish at home. Executive function abilities appeared to be unrelated to preschoolers' bilingual classification, and thus their English vocabulary and letter-word skills. Practice or Policy : The findings have implications for early education programs working to increase the school readiness of Spanish-speaking children by highlighting the key role that effortful control may play in supporting their learning of English skills, particularly for those whose parents speak exclusively Spanish at home.